Powerpenia Should be Considered a Biomarker of Healthy Aging - Sandro R. Freitas; Carlos Cruz-Montecinos; Sébastien Ratel; Ronei S. Pinto (SpringerOpen, 2024)
Abstract To identify biomarkers that precede the decline of human function and independence during the lifespan, two important concepts have been introduced in recent decades: sarcopenia and dynapenia. While the former is originally focused on skeletal muscle loss, the latter is on maximal strength loss. Although the dynapenia concept implies the inclusion of skeletal muscle power, in practical terms, this has not been specifically addressed. For instance, only 2 out of 220 studies published between 2008 and 2023 have directly measured muscle power to classify individuals with dynapenia. As previous studies have shown a greater relevance of skeletal muscle power in healthy aging, we hereby propose the introduction of the term "powerpenia" to specifically reflect the loss of skeletal muscle power along lifespan, but also with disease and/or physical inactivity. Together with sarcopenia and dynapenia, we contend that powerpenia should be considered a biomarker of healthy aging.